2014
DOI: 10.3399/bjgp14x680473
|View full text |Cite
|
Sign up to set email alerts
|

Using a mobile health application to support self-management in COPD: a qualitative study

Abstract: The mHealth applicationThe EDGE (sElf-management anD support proGrammE) COPD project aims to evaluate the efficacy of a multi-component mHealth intervention, delivered via a tablet computer, to improve quality of life in patients with COPD.12 This mHealth intervention focused on simplicity of use (touch screen, no keyboard), and consisted of a symptom diary (Figure 1), 13 remote self-monitoring (pulse oximetry) (Figure 2), and multimedia educational and self-management materials (videos, text, and images).Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 18 publications
(20 reference statements)
9
124
0
2
Order By: Relevance
“…This DHT resource supported self-management and users reported that it helped them to feel more in control of their condition when interviewed 6 months after commencing use of the DHT. These users also reported having a better understanding of what their oxygen saturations should be and less need for reassurance from healthcare professionals (Williams et al 2014). Another example of successful ongoing use is the website-based dizziness management programme reported by Essery et al (2017).…”
Section: Re-evaluating Ongoing Benefitmentioning
confidence: 99%
See 2 more Smart Citations
“…This DHT resource supported self-management and users reported that it helped them to feel more in control of their condition when interviewed 6 months after commencing use of the DHT. These users also reported having a better understanding of what their oxygen saturations should be and less need for reassurance from healthcare professionals (Williams et al 2014). Another example of successful ongoing use is the website-based dizziness management programme reported by Essery et al (2017).…”
Section: Re-evaluating Ongoing Benefitmentioning
confidence: 99%
“…However, literature identifies some very successful DHT introductions that encouraged ongoing use. One example is the study by Williams et al (2014) using a tablet-computer based intervention for people with chronic obstructive pulmonary disease (COPD). This DHT resource supported self-management and users reported that it helped them to feel more in control of their condition when interviewed 6 months after commencing use of the DHT.…”
Section: Re-evaluating Ongoing Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…The past 20 years has seen a huge increase in the use of telephone consultations, 4 and it is likely that the next 20 years will see a similar increase in other forms of consultation, including use of e-mail and telehealth. 2,3,14 It is also likely that the current move from reactive care (where we see the individuals who present most often) towards proactive care (where we identify and target patients with most need) will continue. This will require more sophisticated use of data in electronic medical records to identify patients with greatest healthcare needs.…”
Section: Ehealthmentioning
confidence: 99%
“…81 Earlier qualitative work had also suggested that interacting with a telehealth intervention and receiving feedback from the health professional can increase satisfaction in relation to factors such as continuity of care, understanding of symptom variability and encouragement of self-management behaviour. 82 While participants were mostly positive about their role in telemonitoring, several were glad to hand their devices back at the end of this short (3-6 month) study, stating that they were getting bored using it everyday. This raises the question about long-term sustainability of such interventions requiring regular work by the patients that increase their overall treatment burden.…”
Section: Technology and Copdmentioning
confidence: 99%